Science Videos A User's Manual for Scientific Communication - Vachon, Ryan (Springer International Publishing, 2018)
This book breaks down the critical elements that all introductory film makers must know to make a potent videos for public consumption. Each chapter transports the reader from a place of unknowing to being prepared to build and dissemintate their own video productions. This user's manual gives the reader a complete set of directions for video-making and the wisdom to leverage these skills to inform their intended audience. Effective science communication with the public is no easy task. Math, complex figures and large bodies of technical knowledge present formidible roadblocks for sharing with scientific findings, however certain tools, like video production, help to bridge this gap. .